Circulatory microRNAs as potential biomarkers for fatty liver disease: the Rotterdam study. Issue 3 (27th November 2020) - Zhang, Xiaofang; Mens, Michelle M. J.; Abozaid, Yasir J.; Bos, Daniel; Darwish Murad, Sarwa; de Knegt, Robert J.; Ikram, M. Arfan; Pan, Qiuwei; Ghanbari, Mohsen
Summary: Background: Fatty liver disease (FLD) is the most common cause of liver dysfunction in developed countries. There is great interest in developing clinically valid and minimally invasive biomarkers to enhance early diagnosis of FLD. Aim: To investigate the potential of circulatory microRNAs (miRNAs) as biomarkers of FLD at the population level. Methods: Plasma levels of 2083 miRNAs were measured by RNA sequencing in 1999 participants from the prospective population‐based Rotterdam Study cohort. The Hounsfield Unit (HU) attenuation of liver was measured using non‐enhanced computed tomography (CT) scan. Logistic and linear regression models adjusting for potential confounders were used to examine the association of circulatory miRNAs with liver enzymes (n = 1991) and CT‐based FLD (n = 954). Moreover, the association of miRNAs with hepatic steatosis and liver fibrosis was assessed longitudinally in individuals who underwent abdominal ultrasound (n = 1211) and transient elastography (n = 777) after a median follow‐up of >6 years. Results: Cross‐sectional analysis showed 61 miRNAs significantly associated with serum gamma‐glutamyl transferase and/or alkaline phosphatase levels (Bonferroni‐corrected P  < 8.46 × 10 −5 ). Moreover, 17 miRNAs were significantly associated with CT‐based FLD ( P  < 8.46 × 10 −5 ); 14 were among miRNAs associated with liver enzymes. Longitudinal analysis showed that 4 of these 14 miRNAs (miR‐193a‐5p, miR‐122‐5p, miR‐378d and miR‐187‐3p) were significantly associated with hepatic steatosis ( P  < 3.57 × 10 −3 ) and three (miR‐193a‐5p, miR‐122‐5p and miR‐193b‐3p) were nominally associated with liver fibrosis ( P  < 0.05). Nine of the 14 identified miRNAs were involved in pathways underlying liver diseases. Conclusions: Plasma levels of several miRNAs can be used as biomarkers of FLD, laying the groundwork for future clinical applications.